Financial Reporting Quality, Corporate Governance, and Idiosyncratic Risk: Evidence from a Frontier Market - Linh T.M. Nguyen; Duyen Le; Trang Tran; Tung Dang (Australasian Accounting, Business and Finance Journal, 2021)
We extend current literature by providing empirical evidence on the impacts of financial reporting quality and corporate governance mechanism - two firm-level determinants that are strongly affected by the unique market setting and regulatory framework in emerging/frontier markets - and idiosyncratic risk in Vietnam. Utilizing different panel data analysis techniques, we find high-quality financial reports can mitigate firm-specific risk. Firms with high state ownership tend to have lower idiosyncratic risk too, implying the monitoring role of the government. We also document a positive link between board size and firm specific risk. Our results are thus beneficial for industry regulators and firms in ensuring good governance and reporting framework to better manage firm risk.
Keywords: Idiosyncratic risk; financial reporting quality; corporate governance; Vietnam